Mimbar dan Altar: Kajian Historis Liturgis atas Kesatuan Firman dan Perjamuan Kudus di Ibadah Minggu menurut Martin Luther serta Relevansinya terhadap Ibadah Minggu HKBP - Ricky Pramono Hasibuan; Ricky Pramono Hasibuan (SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora dan Kebudayaan, 2023)
This article seeks to understand the relationship between the Word and the Holy Communion in Sunday Worship. First, this article will do a historical study from the early church era to the Middle Ages. Furthermore, there will be a particular study on the order of Sunday Worship written by Martin Luther, the Formula Missae et Communiones and the Deustsche Messe. Furthermore, this article will look at the theological relationship between the Word and the Holy Communion at Sunday Worship, especially from the Luther and Lutheran perspective. As an implication, this article will elaborate on HKBP Sunday Worship in conjunction with the Lutheran liturgy and the Prussian Agenda.